MEMAHAMI MOTIVASI, BENTUK INTERAKSI, DAN MANFAAT BAGI FOLLOWER DALAM MENGIKUTI MICRO-INFLUENCER DI MEDIA SOSIAL INSTAGRAM - Desynta Kurnia Hapsari; S.Rouli Manalu; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The emergence of social media has brought many changes in people's lives. The increasing use of social media has also increased the emergence of the influencer phenomenon, especially in Indonesia. Micro influencers are the lowest influencer category on social media in terms of the number of followers that range from 1,000 to 15,000 followers. However, despite having the lowest follower count of any other category and not having their former popularity, micro influencers are able to attract an audience to follow them on Instagram. This study aims to understand in depth the motivations of followers to follow certain micro influencers, what forms can be intertwined between the two, as well as the benefits gained by followers in following these micro influencers. This research is a phenomenological research with an Interpretative Phenomenological Analysis (IPA) approach. The data collection technique was carried out using in-depth interview techniques with twelve (12) informants from three (3) different micro influencer categories, with the criteria of actively interacting on social media with the micro influencers they follow. The results of this study found that there were four follower motivations in following micro influencers on social media. First, there is positive emotional arousal in the form of feeling happy, excited, entertained, excited, and motivated. Second, there is physical attractiveness such as the physical appearance of micro influencers, similarities in hobbies, tastes or areas of residence, and the ability of micro influencers to produce content and manage their social media. Third, there is the Bandwagon Effect, where followers tend to follow micro influencers because they follow what their friends are doing. Fourth, followers are motivated to follow micro influencers on social media because they set micro influencers as role models. Meanwhile, the interactions that exist between followers and the micro influencers they follow are parasocial interactions, because closeness is only felt by the followers. By following micro influencers, followers can get benefits in the form of fulfilling their needs for information and entertainment